STRUCTURAL AND GRAMMATICAL CHARACTERISTICS OF PHRASEOLOGICAL UNITS - Seytimbetova Aykumar Pulatbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Phraseology tends to reflect the correlation between language and culture. Therefore, the language user needs shared knowledge in order to be able to understand given units properly. The knowledge of connotative meanings of components enables the language user to decode modifications of canonical forms of phraseological units as well as to create their own modifications. This work deals with structural and grammatical analysis of phraseological units and provides examples.